Correlated responses on cotton fiber traits with the selection for fiber color - Carvalho, Luiz Paulo de; Santos, José Wellington dos (Pesquisa Agropecuaria Brasileira, 2003)
Constant breeding works with the white fiber cotton developed higher cultivars that show better fiber quality than the colored lint ones. The objective of this work was to evaluate the effect of the selection for different color grades on the fiber quality of upland cotton in F5 progenies from the crossing between adapted white fiber cultivars and exotic green and brown germplasm bearing known genes for these lint colors. Most of the fiber traits were negatively correlated with the color fiber and the correlated responses decreased when the selection was made for more intense color of the fiber.